New Techniques of Watermark Images using Bit Plane Slicing and Cubic-spline Interpolation - Dheyauldeen Najeeb, Huda (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
A watermark is a pattern or image defined in a paper that seems as different shades of light/darkness when viewed by the transmitted light which used for improving the robustness and security. There are many ways to work Watermark, including the addition of an image or text to the original image, but in this paper was proposed another type of watermark is add curves, line or forms have been drawn by interpolation, which produces watermark difficult to falsify and manipulate it. Our work suggests new techniques of watermark images which is embedding Cubic-spline interpolation inside the image using Bit Plane Slicing. The Peak to Signal Noise Ratio (PSNR) and Mean Square Error (MSE) value is calculated so that the quality of the original image before and after the data embedding is evaluated.